An Analysis of Students' Difficulties in Speaking English - Rahmi Fhonna; Maskur; Suci Saufa Yuthika (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study focused on analyzing the difficulties faced by students when speaking English at Darul Ulum Islamic Boarding School in Banda Aceh. The study aimed to identify these difficulties and explore the underlying factors contributing to them. A mixed-methods research design was employed, involving questionnaires and interviews. The participant of this research was 21 eleventh-grade students. The findings indicated that students face various challenges in speaking English. They encountered obstacles in grammar (43% expressing concerns), fluency (15% citing regional accents as a barrier), pronunciation (15% experiencing difficulties), and vocabulary (43% uncertain about their proficiency). The study highlighted the need for tailored support to address these issues effectively. Additionally, the research explored factors contributing to these difficulties, including inhibition (43% lacking confidence),